Care Provider Order Entry (CPOE): A Perspective on Factors Leading to Success or to Failure - Ozdas, A.; Miller, R. A. (Yearbook of Medical Informatics, 2007)
Authors provide a perspective on factors leading to successful care provider order entry (CPOE) implementations.Viewpoint of authors supported by background literature review.Authors review both benefits and challenges related to CPOE implementation using three guiding principles: (1) a clinical approach to clinical systems, which claims that CPOE implementation is analogous to a “good” clinician delivering care to a patient; (2) a commitment to quality, which advocates that no compromises should be made in implementing system functionality and clinical system content – the highest objective for CPOE implementation is to provide better quality of care and increased safety for patients; (3) a commitment to fairness, as evidenced by respect for individuals and support of local autonomy, which advocates for minimizing disruptions to clinician-users’ workflows, and adequate local control over CPOE system design and evolution, including clinical content management.Past experiences with CPOE implementation can inform future installation attempts. Sociocultural factors dominate in determining the success of implementation, and should govern technical factors.
Keywords: Medical order entry systems; socioeconomic factors; decision making; organizational; decision support systems; clinical; practice guidelines; hospital information systems; physician’s practice patterns